2019
DOI: 10.1155/2019/6074892
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Offshore Natural Gas Hydrate Dissociation by Depressurization in Marine Sediments

Abstract: Dynamic characteristics of offshore natural gas hydrate (NGH) dissociation will provide the theoretical basis to analyze technical issues of oceanic hydrate exploitation. A mathematical model is developed to simulate offshore NGH dissociation by depressurization in marine sediments. Different phase combination statuses are involved in the process of NGH dissociation by taking ice melting and water freezing into account. The proposed methodology can analyze the processes of hydrate and water phase transitions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Mass Conservation Equations. The mass conservation equation of each component in porous media can be expressed as 29,30…”
Section: Methodsmentioning
confidence: 99%
“…Mass Conservation Equations. The mass conservation equation of each component in porous media can be expressed as 29,30…”
Section: Methodsmentioning
confidence: 99%
“…The mass conservation equation of each component considering the influence of temperature and rock deformation on gas and water flow in porous media can be written as [26,27]:…”
Section: Mass Conservation Equationsmentioning
confidence: 99%
“…[50][51][52] The quick dissociation of NGH leads to several severe problems, such as borehole collapse, effective stress drop, and casing deformation. [53][54][55][56] Oka et al 57 and Kimoto et al 58,59 used numerical methods to predict the deformation of NGH sediments considering the dissociation process of NGH. They found that the soil strength decreased and the rock skeleton stress increases in the NGH dissociation process.…”
Section: Effect Of Hydrate Dissociationmentioning
confidence: 99%